2018
DOI: 10.1186/s13104-018-3650-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating broad-scale system change using the Consolidated Framework for Implementation Research: challenges and strategies to overcome them

Abstract: ObjectiveThe objective of this paper is to demonstrate the utility of the CFIR framework for evaluating broad-scale change by discussing the challenges to be addressed when planning the assessment of broad-scale change and the solutions developed by the evaluation team to address those challenges. The evaluation of implementation of Patient-centered Care and Cultural Transformation (PCC&CT) within the Department of Veterans Affairs (VA) will be used as a demonstrative example. Patient-Centered Care (PCC) is pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…A recent application of the CFIR framework to a Patient-Centered Care "cultural transformation" in the Department of Veterans Affairs (VA) found that the CFIR was a useful starting point but that adapted definitions and a mixed deductive-inductive approach were needed to accommodate the complexity of a broad-scale implementation (Hill et al, 2018). With the adaptations, key findings helped the researchers to understand the individual and organizational factors, barriers and facilitators, and the impact on implementation (Hill et al, 2018). Furthermore, the researchers were able to turn the findings into an easily understood and actionable set of findings and recommendations for stakeholders (Hill et al, 2018).…”
Section: State Targeted Response To the Opioid Crisis (Str) And The Cmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent application of the CFIR framework to a Patient-Centered Care "cultural transformation" in the Department of Veterans Affairs (VA) found that the CFIR was a useful starting point but that adapted definitions and a mixed deductive-inductive approach were needed to accommodate the complexity of a broad-scale implementation (Hill et al, 2018). With the adaptations, key findings helped the researchers to understand the individual and organizational factors, barriers and facilitators, and the impact on implementation (Hill et al, 2018). Furthermore, the researchers were able to turn the findings into an easily understood and actionable set of findings and recommendations for stakeholders (Hill et al, 2018).…”
Section: State Targeted Response To the Opioid Crisis (Str) And The Cmentioning
confidence: 99%
“…With the adaptations, key findings helped the researchers to understand the individual and organizational factors, barriers and facilitators, and the impact on implementation (Hill et al, 2018). Furthermore, the researchers were able to turn the findings into an easily understood and actionable set of findings and recommendations for stakeholders (Hill et al, 2018).…”
Section: State Targeted Response To the Opioid Crisis (Str) And The Cmentioning
confidence: 99%
“…15 While the CFIR framework offers a comprehensive taxonomy of factors influencing intervention planning and implementation, a mixed deductive-inductive approach has been used to address the challenge that CFIR domains and constructs may not capture all emergent themes in qualitative assessment. 16 The deductiveinductive approach integrates inductive, data-driven codes with deductive, theory-driven codes using an a priori code template and has proven rigor within qualitative research. 17 This approach expedites data analysis while providing comprehensive themes that otherwise would not be captured by CFIR constructs.…”
Section: Framework and A Deductive-inductive Coding Approachmentioning
confidence: 99%
“…The NIH Stage Model describes six general stages of translation (from basic research to implementation), but does not provide methodological details for implementing interventions [ 11 ]. Another model, the Consolidated Framework for Implementation Research focuses on a taxonomy used to classify characteristics of the intervention, the inner and outer settings, individuals, and implementation processes, rather than specifying practical methodological steps [ 12 ].…”
Section: Introductionmentioning
confidence: 99%